Experimental study on critical conditions of ground collapse caused by leakage of pressurized hydraulic pipelines in sandy formations - Zhou, Liling; Ping, Qimeng; Shen, Huizhen; Wang, Yiming; Huang, Qing; Zhang, Dazheng (Frontiers in Earth Science, 2026)
Ground collapse poses a significant threat to urban safety, and pipeline leakage in sandy formations is an important factor that triggers it. A series of physical experiments was designed to explore the process, especially the critical conditions of ground collapse caused by leakage of pressurized water pipes. According to the test results, under different combinations of compactness of sand and water flow velocity in the pipeline, three final states of sandy formations under pipeline leakage erosion were identified: infiltration disturbance, stable cavity, and fluidization failure. Then, the critical conditions between the state of stable cavity and fluidized failure were obtained, which can be used for predicting ground collapse caused by pipeline leakage. Thirdly, a model for predicting the scale (volume and area) of ground collapse was built by logarithmic regression analysis. Finally, a ground collapse early warning model was proposed based on the correspondence between surface subsidence monitoring data and the area of cavities in the sandy formation during the experimental process. The research results can serve as a scientific basis for the prevention and control of urban ground collapse.